On the enumeration of the set of saturated numerical semigroups of a given genus - Branco, M.B. (2014)
In this paper we present an algorithm for computing the set of saturated numerical semigroups of a given genus. We see how the set of saturated numerical semigroups can be arranged in a tree rooted in N and we describe the sons of any vertex of this tree.